Arsenic mobilization from iron oxides in the presence of oxalic acid under hydrodynamic conditions. (December 2018) - Sun, Jing; Bostick, Benjamin C.; Mailloux, Brian J.; Jamieson, James; Yan, Beizhan; Pitiranggon, Masha; Chillrud, Steven N.
Abstract: Oxalic acid potentially enhances pump-and-treat for groundwater As remediation by accelerating mobilization. This study examines how oxalic acid mobilizes As from Fe(III)-oxide coated sand under hydrodynamic conditions. Four columns were packed with metal-substituted ferrihydrite or goethite to 1% Fe, presorbed to 50% As surface coverage, and reacted with pH = 2.2 artificial groundwater amended with 10 mM oxalic acid at 1 m day −1 . Arsenic elution was affected by both As and Fe speciation. Although the As(V) columns experienced faster substrate dissolution, As(V) elution was delayed by re-adsorption, whereas As(III) elution was rapid due to pH decrease that prevented re-adsorption. Cr-ferrihydrite and Ni-goethite dissolved both effectively initially but then diverged. The Cr-ferrihydrite columns experienced continuous stoichiometric Fe and Cr release, and As release could be sustained. The Ni-goethite columns initially experienced nonstoichiometric Fe and Ni release, and As release was extensive. Such release, however, was not sustained. We hypothesized that Ni-goethite contained sites with distinct reactivity, and oxalic acid targeted readily-dissolved, sorption-dense sites. Our data indicate that oxalic acid-enhanced pump-and-treat methods would be easier to apply to aquifers dominated by As(III), requiring less amendment to be injected; such oxalic acid-enhanced methods remove reactive sediment Fe and As, potentially preventing future groundwater contamination. Graphical abstract: Highlights: We study oxalic acid promoted metal release from As presorbed Fe oxide coated sand. Cr and Ni substituted ferrihydrite and goethite were used. The effect of substrate dissolution was isolated from other As release mechanisms. As(V) elution was retarded, whereas As(III) elution was rapid due to pH decrease. Unlike Cr-ferrihydrite, metal release from Ni-goethite could not be sustained.